Comprehensive genomic and transcriptomic analysis enables molecularly guided therapy options in peritoneal and pleural mesothelioma - Möhrmann, Lino; Werner, M.; Oleś, M.; Knol, L.; Arnold, J. S.; Mundt, T.; Paramasivam, N.; Richter, D.; Fröhlich, M.; Hutter, Barbara; Hüllein, J.; Jahn, A.; et al. (ESMO open, 2025)
Introduction - Peritoneal, pericardial and pleural mesothelioma (PeM/PcM/PM) are rare and aggressive diseases with limited survival. Molecularly guided therapy is currently not part of standard care. - Methods - This study integrates molecular and clinical data from 51 patients (among them 28 PM, one PcM, 21 PeM and one synchronous PeM/PM) enrolled in the National Center for Tumor Diseases and the German Cancer Consortium (NCT/DKTK) Molecularly Aided Stratification for Tumor Eradication Research (MASTER), a multicenter precision oncology registry trial addressing adults with rare advanced-stage cancers. Analysis comprised both somatic and germline whole exome sequencing/whole genome sequencing and transcriptome analysis leading to personalized treatment recommendations issued by a dedicated molecular tumor board. To assess clinical efficacy, progression-free survival (PFS) ratios comparing molecularly informed therapies (PFS2) to preceding systemic therapies (PFS1) were calculated. Efficacy of immune checkpoint inhibition applied during the observation period was assessed accordingly. - Results - Cancer-related genes altered in more than 5 out of 44 assessable patients were BAP1, CDKN2A, NF2, SETD2 and TP53. Somatic (n = 23) or germline (n = 9) alterations in homologous recombination-related genes were detected in 27/44 patients. In 21/44 cases, they were supported by positive combined homologous recombination deficiency scores or BRCAness signature. Following American College of Medical Genetics and Genomics guidelines, (likely) pathogenic germline variants in autosomal dominant cancer predisposition genes were found in 8/51 patients. Molecular tumor board recommendations were issued in 46 cases and applied in 6 cases. Mean PFS ratio was 2.45 (n = 5). Median PFS2 was 6.5 months (n = 6), median PFS1 was 4.0 months (n = 5). A total of 27 patients received immune checkpoint inhibition during the observation period leading to a mean PFS ratio of 1.69 (n = 19). - Conclusions - In mesothelioma, comprehensive molecular analysis can provide valuable clinically actionable information. Molecularly informed therapy recommendations can lead to clinical benefit.
Online verfügbar 1 April 2025, Version des Artikels 1 April 2025
Gesehen am 13.10.2025